Birth - Spirn, Michele (Woodbridge, Conn. : Blackbirch Press, 1999)
Describes how people in various countries around the world celebrate the birth of babies.
Includes bibliographical references (p. 24) and index.
L.A. Recommended Foreign Language.
6.1.
6.1
3-6
Keywords: Birth customs -- Juvenile literature; Birth customs; Birth customs